STUDI KASUS: COGNITIVE BEHAVIOR THERAPY UNTUK MENGURANGI KECENDERUNGAN KECEMASAN SOSIAL PADA SISWA SEKOLAH DASAR - Berliana, Azirna; Nurtjahjo, Fani Eka (MANASA, 2024)
Excessive feelings of fear characterize students with social anxiety and worry and avoidance of social situations, especially in the school environment. Students quickly feel nervous and anxious when they are in a crowded environment or public place, such as avoiding appearing in front of the class, not daring to refuse or reprimand others, speaking in a low voice, not daring to answer or ask questions, not looking the other person in the eye, and being afraid. Others poorly view them. This case study involves a fifth-grade elementary school (Sekolah Dasar/SD) student who has experienced social anxiety for the past year. The subject feels uncomfortable in crowded places and has negative thoughts about other people's views of him. Assessment is carried out by observation, interviews, psychological tests (WISC, CSCT, graphic), and the Liebowitz social anxiety scale. The intervention provided to reduce social anxiety in subjects used a cognitive-behavioral approach, namely, Cognitive Behavior Therapy, carried out for nine sessions. The intervention results showed that the subjects could identify irrational thoughts and change them to be more rational, decreasing anxiety levels when appearing in front of the class and interacting with other people in the class and school environment according to the predetermined intervention targets.